Quantitative variation in Drosophila melanogaster wing shape and size - Pelletier, Katharine (My University, 2023)
Several studies examining the genetics of adaptation have identified single alleles, of large phenotypic e ect, contributing to divergence between populations. This empirical finding is consistent with predictions made by the geometric model of adaptation, where a small number of alleles of large e ect and many alleles of small e ect are fixed as the population adapts. However, these examples of single genes of large e ect may represent a biased sample of the alleles of adaptation with polygenic allele shifts having a greater contribution than currently understood. Increasing power to detect smaller e ect variants, due to falling sequencing costs and improved statistical methods, has made the contribution of small allele frequency shifts at many loci, or polygenic adaptation, more apparent. In contrast to models predicting single genes of large e ect with large allele frequency changes, polygenic adaptation allows for small allele frequency changes across many alleles of small e ect to contribute to phenotypic change. Using artificial selection, I demonstrate the alignment of genetic e ects contributing to wing shape variation within a developmental pathway but a lack of replication of these same genetic e ects in other wild-caught populations. Secondly, using advanced intercross QTL mapping between altitudinally diverged populations, I demonstrate a polygenic basis for wing shape and size variation. Finally, using comparative developmental biology I investigate how change to cell size and number in the wing may contribute to divergence between high and low altitude populations. Together, this work provides evidence for many alleles of small e ect rather than alleles of large e ect contributing to adaptive divergence of wing shape and size and provides context for identified alleles through replication in other populations and comparative developmental biology.
Keywords: Quantitative Genetics; Drosophila; Multivariate Traits; Development; Genetics; Genetics of complex traits